Mobility of Goods and People at the Port of Murhum Baubau, 1988-2012 - Sabahrudin La Ode Mago; Singgih Tri Sulistiyono; Yety Rochwulaningsih (Diponegoro University, 2020)
This paper discusses the mobility of goods and people at the Port of Murhum Baubau during 1988-2012. This port has an important role in the process of mobility of goods and people in Southeast Sulawesi. This paper also addresses the issue of how the mobility of goods and people both in Southeast Sulawesi, national, and international through the Murhum Baubau Port in the period 1988-2012. To analyze these problems, the author applied historical to proof the major development of the Post of Murhum that functiones as mobility of goods and people passing the port of Murhum Baubau in regional, national, and international could be studied comprehensively, especially exploring some primary sources that coming from the oficials and other institution. In addition, the Port of Murhum is also considered important because it is a gateway for sea transportation, loading and unloading of goods, and transit points for passengers from various regions in Indonesia, both from eastern and western Indonesia. The term of Southeast Sulawesi used in this paper refers to the region between east and south of Sulawesi Island. This region has a strategic position in connecting eastern and western regions of Indonesia. The market commodities from the Baubau region are nickel, asphalt, bitumen, chrome, and fish. In addition, the mobility of goods and people from the Southeast Sulawesi region has a fluctuating increase periodicly.